(untitled) (Revista Paradigma, 2022)
This article seeks to analyze the theories of Axel Honneth and Nancy Fraser in the face of struggles for recognition in contemporary times, and to assess the extent to which affirmative actions and judicial activism constitute instruments for the realization of rights. Thus, at first, the right to recognition is considered, realizing that in the second half of the 20th century, especially after the collapse of the Union of Soviet Socialist Republics and the socialism it advocated, class struggles were replaced by struggles for recognition intersubjective. On the one hand, Honneth argues that disrespect regarding lack of recognition is the root of social conflicts and, therefore, the driving force for social movements; on the other hand, Fraser, in turn, works with two perspectives: recognition and redistribution, arguing that the lack of recognition does not necessarily imply economic inequality. The fact is that the right to recognition has been subject to judicialization and, not infrequently, has received activist responses. From the research it was possible to conclude that, if on the one hand the judicialization arises from the phenomenon of constitutionalization of the law, activism, on the other hand, attacks against institutional stability, the separation of powers and democracy itself. In turn, both recognition and redistribution face obstacles in terms of changing social structures, making transformative action in social reality necessary. The method used was the analytical-deductive one, with fulcrum in books and scientific articles.